2022
DOI: 10.3389/fphys.2022.1008640
|View full text |Cite
|
Sign up to set email alerts
|

Ionizing radiation, cerebrovascular disease, and consequent dementia: A review and proposed framework relevant to space radiation exposure

Abstract: Space exploration requires the characterization and management or mitigation of a variety of human health risks. Exposure to space radiation is one of the main health concerns because it has the potential to increase the risk of cancer, cardiovascular disease, and both acute and late neurodegeneration. Space radiation-induced decrements to the vascular system may impact the risk for cerebrovascular disease and consequent dementia. These risks may be independent or synergistic with direct damage to central nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 219 publications
0
2
0
Order By: Relevance
“…Deep space missions inherently involve dramatic increases in exposure to highly charged and energetic (HZE) ionizing radiation, which affects cellular function. Dose-relevant radiation studies have revealed direct effects on neuronal tissue ( Raber et al, 2016 ; Jandial et al, 2018 ), functional decrements ( Vlkolinsky et al, 2010 ; Blackwell et al, 2022 ), as well as oxidative stress and neuroinflammation ( Zwart et al, 2021 ; Holley et al, 2022 ; Miller et al, 2022 ; Verma et al, 2022 ). Neuroinflammation is in turn associated with a wide range of maladies—including neurodegenerative diseases such as Alzheimer’s, Parkinson’s, and Huntington’s diseases ( Teleanu et al, 2022 ).…”
Section: The Brain In Spacementioning
confidence: 99%
“…Deep space missions inherently involve dramatic increases in exposure to highly charged and energetic (HZE) ionizing radiation, which affects cellular function. Dose-relevant radiation studies have revealed direct effects on neuronal tissue ( Raber et al, 2016 ; Jandial et al, 2018 ), functional decrements ( Vlkolinsky et al, 2010 ; Blackwell et al, 2022 ), as well as oxidative stress and neuroinflammation ( Zwart et al, 2021 ; Holley et al, 2022 ; Miller et al, 2022 ; Verma et al, 2022 ). Neuroinflammation is in turn associated with a wide range of maladies—including neurodegenerative diseases such as Alzheimer’s, Parkinson’s, and Huntington’s diseases ( Teleanu et al, 2022 ).…”
Section: The Brain In Spacementioning
confidence: 99%
“…More recently, researchers have identified cerebral microbleeds (CMBs) as potential indicators of damage resulting from the cerebrovascular risks associated with spaceflight ( Hähnel, 2020 ; Miller et al, 2022 ). Cerebral microbleeds are microhemorrhages (<10 mm in diameter) in the brain, producing covert lesions, and are visible as small hypointense foci on T 2 *-weighted gradient-recalled echo (GRE) and similar MRI sequences ( Puy et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%